Relationship Between Physical Activity and Personal Hygiene with Pathological Leukorrhea in Female Sports Students - TITANIA ARFINISA KIRANA; BAMBANG PURWANTO; WAHYUL ANIS (HANG TUAH MEDICAL JOURNAL, 2022)
Background: Women's reproductive health must receive serious attention, especially a problem that is often experienced by most women, namely leukorrhea. These problems are often ignored and taken lightly, even though if handled too late it can be very fatal. In Indonesia, more than 80% of vaginal discharge complaints are pathological. Analysing of the risk factors for pathological vaginal discharge can be the first step in preventing leukorrhea early, especially in the community of women who are active in sports. Methods: This study used observational analytic with a cross-sectional approach. The sample size is 70 sports students in Surabaya. The sampling technique used is simple random sampling. Data were analyzed using the chi-square test on SPSS. Results: The results showed that there was no relationship between the level of physical activity; frequency of changing underwear; the use of underwear material; use of vaginal cleansing soap; and the use of panty liners with the event of pathological leukorrhea (p-value > 0.05). But there is a relationship between the way of washing the vagina with the incidence of pathological leukorrhea (p-value 0.007). Conclusion: The risk factor that has a significant relationship with the incidence of pathological leukorrhea is how to wash the vagina. Meanwhile, other factors such as the level of physical activity, the frequency of changing underwear, the use of underwear material, the use of vaginal soap/antiseptic, and the use of panty liners have no relationship with the incidence of pathological leukorrhea in female sports study program students in Surabaya. Keywords : risk factor, activity, vaginal hygiene, leukorrhea